2009
DOI: 10.1007/s11145-009-9213-7
|View full text |Cite
|
Sign up to set email alerts
|

Developmental dyslexics show deficits in the processing of temporal auditory information in German vowel length discrimination

Abstract: The present study investigated auditory temporal processing in developmental dyslexia by using a vowel length discrimination task. Both temporal and phonological processing were studied in a single experiment. Seven German vowel pairs differing in vowel height were used. The vowels of each pair differed only with respect to vowel length (e.g., /a/ vs. /a:/). In German, vowel length is characterized by temporal and spectral information. Three types of differences between long versus short vowels were varied: In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 73 publications
2
21
0
Order By: Relevance
“…In dyslexics, poor speech perception manifests itself as difficulties to discriminate and categorize speech sound contrasts like syllables, consonants and vowels (e.g., . Nevertheless, there are studies that fail to find differences between dyslexics and controls for some speech contrasts (Blomert et al, 2004;Groth et al, 2011). For example, Groth et al (2011) found that dyslexics were poorer in discriminating longer vowels from shorter ones if they were made shorter by manipulation (only durational cues available), but they found no group effect for naturally shorter versus longer vowels (both spectral and durational cues available).…”
Section: Speech Perception Related Brain Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…In dyslexics, poor speech perception manifests itself as difficulties to discriminate and categorize speech sound contrasts like syllables, consonants and vowels (e.g., . Nevertheless, there are studies that fail to find differences between dyslexics and controls for some speech contrasts (Blomert et al, 2004;Groth et al, 2011). For example, Groth et al (2011) found that dyslexics were poorer in discriminating longer vowels from shorter ones if they were made shorter by manipulation (only durational cues available), but they found no group effect for naturally shorter versus longer vowels (both spectral and durational cues available).…”
Section: Speech Perception Related Brain Responsesmentioning
confidence: 99%
“…Nevertheless, there are studies that fail to find differences between dyslexics and controls for some speech contrasts (Blomert et al, 2004;Groth et al, 2011). For example, Groth et al (2011) found that dyslexics were poorer in discriminating longer vowels from shorter ones if they were made shorter by manipulation (only durational cues available), but they found no group effect for naturally shorter versus longer vowels (both spectral and durational cues available). Further, using functional magnetic resonance imaging (fMRI), Steinbrink et al (2012) observed decreased activation of left inferior frontal gyrus and insular cortices in dyslexics during processing of the same temporal stimuli, but only in the subgroup of low performing dyslexics (Steinbrink et al, 2012).…”
Section: Speech Perception Related Brain Responsesmentioning
confidence: 99%
“…However, preliterate children at risk for dyslexia have been found to exhibit an atypical lateralization for this oscillatory frequency band (Vanvooren et al, 2014). Phoneme discrimination has proven to be a confident criterion for differentiating poor and normal reading abilities (Hämäläinen et al, 2009, Brunner, Bäumer, Rosenauer, Scheller, & Plinkert, 2010Groth, Lachmann, Riecker, Muthmann, & Steinbrink, 2011;Steinbrink, Klatter, & Lachmann, 2014), and in fact, this is an ability that emerges very early during language 14 acquisition (Kuhl, 1979;Shahidullah & Hepper, 1994;Cheour-Luhtanen et al, 1995).…”
Section: Brain Rhythms As Biomarkers Of Dyslexiamentioning
confidence: 99%
“…In addition, fMRI has been used extensively to analyze brain functionality in dyslexia during phonological processing [216][217][218][219][220][221][222]. For example, Shaywitz et al [216] analyzed fMRI activation patterns of 26 dyslexic subjects and 23 control subjects during a phonological analysis task.…”
Section: Functional Magnetic Resonance Imaging (Fmri) Is a Noninvasivmentioning
confidence: 99%
“…The control subjects exhibited activation in the left middle temporal gyrus area, whereas this area showed disturbed activity in dyslexics. Groth et al [219] used fMRI to study the auditory temporal and phonological processing in dyslexic individuals using a German vowel length discrimination task. Dyslexic subjects performed worse than controls in response to temporal processing, whereas they did not differ in response to phonological processing.…”
Section: Functional Magnetic Resonance Imaging (Fmri) Is a Noninvasivmentioning
confidence: 99%